2000
DOI: 10.1186/ar80
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of T cells in synovial fluid: high frequencies of CD8+ T cells that are specific for certain viral epitopes

Abstract: Statement of findingsCD8 + T cells dominate the lymphocyte population in synovial fluid in chronic inflammatory arthritis. It is known that these CD8 + T cells are often clonally or oligoclonally expanded, but their specificity and their relevance to the pathogenesis of joint disease has remained unclear. We found that as many as 15.5% of synovial CD8 + T cells may be specific for a single epitope from an Epstein-Barr virus lytic cycle protein. The virus-specific T cells within the joint showed increased expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Previously, it has been shown that, in synovial fluid of patients with chronic inflammatory arthritis, Epstein-Barr virus (EBV) peptide-specific CD8+ T cells can be found [29]. Moreover, CD8+ T cells contribute to osteoarthritis progression via cartilage degeneration in an animal model [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that, in synovial fluid of patients with chronic inflammatory arthritis, Epstein-Barr virus (EBV) peptide-specific CD8+ T cells can be found [29]. Moreover, CD8+ T cells contribute to osteoarthritis progression via cartilage degeneration in an animal model [30].…”
Section: Discussionmentioning
confidence: 99%
“…As gp110 is important in viral entry during infection of B-cells and epithelial cells, a decreased gp110-specific T-cell response could be speculated to reduce the control of EBV and also enhance spreading of the EBV infection in RA patients. Contrarily, CD8+ cytotoxic T-cells specific for the two lytic cycle EBV antigens, BZLF1 and BMLF1, have been detected in synovial fluid and synovial membranes of RA patients, indicating a contribution of infiltrated cytotoxic T-cells specific for EBV lytic cycle antigens in joint inflammation [84, 85]. …”
Section: Ebv In Sadsmentioning
confidence: 99%
“…In RA patients, the EBV-infected cells in the synovial joints are shown to undergo frequent reactivation including EBV-infected plasma cells producing CCP autoantibodies [72, 7476, 78, 84, 85]. The EBV reactivation results in production of lytic cycle proteins giving rise to host immune responses that presumably contribute to the inflammation and destruction of exocrine glands and synovial joints in SS and RA patients, respectively [72, 7476, 78, 84–90, 96].…”
Section: Genetic Factors and Possible Mechanisms Associated With Imentioning
confidence: 99%
“…Using tetramer staining, one study demonstrated EBV-specific CD8+ T cells in synovial fluid from RA patients. However, these findings were not restricted to RA as there was also an enrichment of these cells in synovial fluid from patients with osteoarthritis and psoriatic arthritis [53]. …”
Section: Pathogenesis Of Lgl Leukemia and Felty’s Syndromementioning
confidence: 99%